The impact of gender demography on male and female role interpretations and contributions: A qualitative study of non-executive directors of Icelandic boards - Jonsdottir, Thoranna (Cranfield University, 2010)
This thesis, submitted for the Cranfield DBA programme, examines and explores the impact of gender demography on male and female director’s role interpretations and contributions. The study was inspired by the scarcity of females on corporate boards and a desire to seek an understanding of how women and men contribute to boards. The study brings together the literature on females on boards, and on board roles and processes, revealing that both bodies of literature could benefit from more in-depth understanding of board processes. The thesis reports the results of two empirical studies based on in-depth interviews with male and female non-executive directors on Icelandic corporate boards. The first study of non-executives of male dominated boards supported many of the findings reported in earlier studies. Females were found to be active in critical questioning and pushing for better decision making. Males on the other hand stressed the importance of informal interactions. The study offered an understanding of the exclusion and low social and power status of females on male dominated boards. The second study, conducted two years later, on non-executives on both male dominated as well as gender integrated boards and an all female board, revealed in much more detail the nature of traditional board interactions and the benefits of a more balanced composition or even an all female composition. Males on gender integrated boards adopted the valuable role of questioning and holding management accountable, previously found to be mainly adopted by females. In addition, a shared understanding of roles and purpose between males and females was found to prevail on those boards. The gender integrated boards and the all female board possessed a much higher degree of openness, interaction and trust, resembling to a large extent the description of exemplary boards found in the literature, and the females on those boards were found to be quite confident. Finally, the findings question if the importance of informal relationships can be generalised, as those were found to have no relevance on gender integrated and all female boards. The study adds to the growing body of literature on board roles and processes, and the female board literature, and has significant implications for practice. It reveals the shortcomings of male dominated boards and challenges them to fundamentally change the ways they act and perform. It demonstrates how female non-executive directors bring valuable contributions and that a better gender balance can positively affect the dynamics of the board.